2022
DOI: 10.1021/jacs.2c02666
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Synthesis and Discovery of Covalent Organic Framework Photocatalysts for Hydrogen Peroxide Production

Abstract: A high-throughput sonochemical synthesis and testing strategy was developed to discover covalent organic frameworks (COFs) for photocatalysis. In total, 76 conjugated polymers were synthesized, including 60 crystalline COFs of which 18 were previously unreported. These COFs were then screened for photocatalytic hydrogen peroxide (H2O2) production using water and oxygen. One of these COFs, sonoCOF-F2, was found to be an excellent photocatalyst for photocatalytic H2O2 production even in the absence of sacrificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
205
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(212 citation statements)
references
References 29 publications
6
205
0
1
Order By: Relevance
“…17,18 The observed effects might be negligible in very dilute solutions of benzyl alcohol, but they might represent a dominant mechanism under solvent-free (only benzyl alcohol) or biphasic (e.g., equivolumetric benzyl alcohol/water mixtures) conditions. [38][39][40][41][42][43] Two further points are noteworthy with respect to the visible light activity. Firstly, the designation of a 420 nm cut-off filter implies, per definitionem, that the transmittance at 420 nm is 50%, i.e., there can be a small portion of higher energy light still transmitted when using these filters.…”
Section: Does Benzaldehyde Once Formed Undergo Further Transformation...mentioning
confidence: 97%
“…17,18 The observed effects might be negligible in very dilute solutions of benzyl alcohol, but they might represent a dominant mechanism under solvent-free (only benzyl alcohol) or biphasic (e.g., equivolumetric benzyl alcohol/water mixtures) conditions. [38][39][40][41][42][43] Two further points are noteworthy with respect to the visible light activity. Firstly, the designation of a 420 nm cut-off filter implies, per definitionem, that the transmittance at 420 nm is 50%, i.e., there can be a small portion of higher energy light still transmitted when using these filters.…”
Section: Does Benzaldehyde Once Formed Undergo Further Transformation...mentioning
confidence: 97%
“…These observations suggested that C 5 N 2 exhibited high intrinsic selectivity in O 2 reduction to H 2 O 2 . Moreover, to our knowledge, C 5 N 2 demonstrated by far the highest H 2 O 2 photocatalytic activity under hypoxic conditions among polymeric photocatalysts (Figure 4b) [2c,d, 12b, 14, 23f,j,m, 28] . The high activity could be explained as follows: accompanying the exceptionally low CB position, the VB position of C 5 N 2 was also relatively low (Figure 2d), at which WOR would be more kinetically favorable.…”
Section: Resultsmentioning
confidence: 80%
“… a) Photocatalytic H 2 O 2 production of C 5 N 2 with different concentrations of dissolved oxygen. b) Summary of photocatalytic activity of H 2 O 2 production in a hypoxic microenvironment by different metal‐free polymers in the literature [2c,d, 12b, 14, 23f,j,m, 28] . c) Photocatalytic H 2 O 2 production of C 5 N 2 with an electron acceptor (AgNO 3 , 0.1 M) or an electron donor (TEOA, 10 % v/v).…”
Section: Resultsmentioning
confidence: 99%
“…Conjugated organic polymers (COPs) with semiconductor properties have attracted extensive interest as a complement to the inorganic counterpart due to their high surface area, tunable photoelectric responsiveness, and extended π-conjugated structure. − The synthesis mode modules provide rich options for photocatalytic applications to regulate porosity, electronic/band structures, and interface properties at the molecular level. , The unique π-conjugated structure endows them with rather improved visible light harvesting and expedited photo-excited charge carrier separation/migration due to large delocalization, presenting exciting potential in artificial photosynthesis . With constant efforts, a variety of COP-based photocatalytic systems with outstanding structures and properties have been developed rapidly, which can promote efficient O 2 reduction to generate H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Anthraquinone (AQ) is a desirable redox center for H 2 O 2 synthesis, although the conventional anthraquinone method is criticized due to the involvement of substantial energy input, severe environmental contamination, and significant safety issues . Attractively, the synthesis mode modules of COPs enable homogeneous incorporation of anthraquinone moieties into π-conjugated frameworks by deliberate selection of building blocks including anthraquinone at the molecular level. , The anthraquinone moieties in COPs can serve as efficient redox centers for photocatalytic H 2 O 2 generation from H 2 O and O 2 , which captures electrons from the COP conduction band (CB) under the irradiation of visible light and subsequently shifts electrons to trigger the electronic coupling hydrogenation reaction (AQ to AQH 2 ); this is a critical process in photocatalytic H 2 O 2 production . However, the pre-designable functionalities of COPs with task-specific anthraquinone moieties for photocatalytic H 2 O 2 production from H 2 O and O 2 have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%